Sacarificación enzimática de la holocelulosa presente en el raquis del banano para obtener azucares fermentables. - Duarte Castillo, Evelyn Alejandra; Herrera Mantuano, Nicole Evelyn (My University, 2024)
This research analyses the use of banana rachis as a raw material to obtain fermentable sugars by means of physical-chemical treatments and enzymatic saccharification. Banana production generates a large amount of agro-industrial waste, this raw material represents a by-product with a high content of lignocellulosic compounds, which makes it a viable option for the production of by-products such as fermentable sugars. The main problem lies in the rachis, which is an agro-industrial waste that is little used, accumulating in plantations and production centres without adequate management. This represents an environmental and economic challenge, but also an opportunity for the valorisation of this waste through biotechnological processes. However, the high content of the lignocellulosic structure hinders the efficient conversion of its components into fermentable sugars. To overcome this barrier, different treatments were applied, followed by enzymatic hydrolysis with Trichoderma reesei, a fungus widely used in lignocellulosic wall degradation. The application of appropriate pre-treatments is key to optimise the conversion of lignocellulosic biomass into sugars. This study contributes to the valorisation of agricultural waste and the development of sustainable processes in the agro-industrial industry; the results showed that the electrolysis treatment presented the highest efficiency in enzymatic hydrolysis, reducing the recalcitrance of the rachis and improving the accessibility of the enzymes. Statistical analysis (ANOVA) confirmed significant differences in the efficiency of the treatments. It was concluded that banana rachis has a high potential for the production of fermentable sugars.
La presente investigación analiza el aprovechamiento del raquis de banano como materia prima para la obtención de azúcares fermentables mediante tratamientos físico-químicos y sacarificación enzimática. La producción de banano genera una gran cantidad de residuos agroindustriales, esta materia prima antes mencionada representa un subproducto con alto contenido de compuestos lignocelulósicos, lo que lo convierte en una opción viable para la producción de subproductos como lo son azucares fermentables. El problema central radica en el raquis, este es un residuo agroindustrial poco aprovechado, acumulándose en plantaciones y centros de producción sin una previa gestión adecuada. Esto representa un desafío ambiental y económico, pero también una oportunidad para la valorización de estos residuos mediante procesos biotecnológicos. Sin embargo, el alto contenido de la estructura lignocelulósica dificulta la conversión eficiente de sus componentes en azúcares fermentables. Para superar esta barrera, se aplicaron distintos tratamientos, seguidos de hidrólisis enzimática con Trichoderma reesei, un hongo ampliamente utilizado en la degradación de la pared lignocelulósica. La aplicación de pretratamientos adecuados es clave para optimizar la conversión de biomasa lignocelulósica en azúcares. Este estudio contribuye a la valorización de residuos agrícolas y al desarrollo de procesos sostenibles en la industria agroindustrial; los resultados mostraron que el tratamiento electrolisis presentó la mayor eficiencia en la hidrólisis enzimática, reduciendo la recalcitrancia del raquis y mejorando la accesibilidad de las enzimas. El análisis estadístico (ANOVA) confirmó diferencias significativas en la eficiencia de los tratamientos. Se concluyó que el raquis de banano tiene un alto potencial para la producción de azucares fermentables.
Keywords: RAQUIS DE BANANO; BIOMASA LIGNOCELULOSICA; SACARIFICACION ENZIMATICA; BIOPRODUCTOS; AZUCARES FERMENTABLES